2012
DOI: 10.1038/ejhg.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense mutation in the signal peptide of the human POMC gene: a possible additional link between early-onset type 2 diabetes and obesity

Abstract: Rare mutations in several genes have a critical role in the control of homeostatic mechanisms such as food-intake, energy balance and glucose metabolism. In this study, we performed a mutational screening in a 58-year-old woman presenting early-onset type 2 diabetes and central obesity. The entire coding regions of MC4R, MC3R, HNF1A, GCK and POMC (pro-opiomelanocortin) genes were analyzed by direct sequencing. A new missense mutation was identified within the POMC gene signal peptide sequence, resulting in a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
(55 reference statements)
1
18
0
1
Order By: Relevance
“…In the present study, ob/ob mice displayed similar abnormal glucose and lipid metabolism and oxidative stress, which were highly consistent with our previous studies in overweight adolescents [14] and clinical studies that have indicated that obese patients are more susceptible to impaired glucose tolerance and an early-onset diabetes [15]. Recent studies by Gurzov et al have reported that oxidative stress accompanying obesity inactivates proteintyrosine phosphatases (PTPs) in the liver, thus activating select signaling pathways that exacerbate disease progression [16].…”
Section: The Impairment Of β Cell Function Induced By Oxidative Stressupporting
confidence: 93%
“…In the present study, ob/ob mice displayed similar abnormal glucose and lipid metabolism and oxidative stress, which were highly consistent with our previous studies in overweight adolescents [14] and clinical studies that have indicated that obese patients are more susceptible to impaired glucose tolerance and an early-onset diabetes [15]. Recent studies by Gurzov et al have reported that oxidative stress accompanying obesity inactivates proteintyrosine phosphatases (PTPs) in the liver, thus activating select signaling pathways that exacerbate disease progression [16].…”
Section: The Impairment Of β Cell Function Induced By Oxidative Stressupporting
confidence: 93%
“…Knockout of the MC4 receptor also results in obesity in rodents (Huszar et al, 1997). In parallel, severe human obesity can be caused by mutations in genes coding for POMC or its melanocortin receptors (Hager et al, 1998; Yeo et al,2000; Krude et al,2003; Mencarelli et al, 2012). …”
Section: Neuropeptide Modulation Of Gaba and Glutamate Synaptic Actionsmentioning
confidence: 99%
“…NPY deficiency attenuates responses to a palatable high fat diet in mice (Hollopeter et al, 1998;Patel et al, 2006). Animals in which POMC neurons have been knocked out are obese and hyperphagic (Butler and Cone, 2002;Mencarelli et al, 2012;Diané et al, 2014;Raffan et al, 2016). Additionally, the release of these neuropeptides is closely associated with dietary fat level.…”
Section: Introductionmentioning
confidence: 99%